Prognosis of Eating and Swallowing Dysfunction Following Brain Injury in a Convalescent Rehabilitation Ward - TAKEDA, Yuki; MAESHIMA, Shinichiro; OSAWA, Aiko; NISHIO, Daisuke; KIGAWA, Hiroshi (The Japanese Journal of Dysphagia Rehabilitation, 2010)
Purpose: The purpose of this study was to investigate the relationship between the bedside swallowing assessment (BSA) on admission and prognosis of eating and swallowing dysfunction on discharge in a convalescent rehabilitation ward.Subjects and Methods: The subjects were 93 patients aged between 18 and 93 years, including 54 males and 39 females, who were hospitalized in a convalescent rehabilitation ward and who received rehabilitation for dysphagia. They consisted of 33 patients with cerebral hemorrhage, 41 patients with cerebral infarction, 10 patients with subarachnoid hemorrhage, and 9 patients with traumatic head injury.We compared the following factors: clinical features, cognitive function, swallowing function, activities of daily living (ADL), and discharge in patients who resumed a regular diet (oral intake group) and those who required tube feeding (tube feeding group).Results: After completion of an inpatient rehabilitation program, 64 patients resumed a regular diet. Twenty-nine patients required tube feeding. The oral intake group was younger and they had higher Mini-Mental State Examination score and Raven's Coloured Progressive Matrices score than the tube feeding group. On the BSA, 13 patients had a normal gag reflex and there were 32 patients in whom the repetitive saliva swallowing test was good on admission, with the oral intake group tending to be better than the other group. There was no difference between the two groups in the period from onset, the period of hospitalization in our hospital, and the score of the modified water swallowing test on admission. In addition, the patients of the oral intake group could start the training with diet by 5 weeks at the latest and could resume some food three times a day by 10 weeks at the latest after hospitalization.The ADL score in the oral intake group was higher than that in the tube feeding group. More patients in the oral intake group could return home. Even the patients with low ADL scores were able to return home if they could resume a regular diet.Conclusion: We considered that it is possible to predict the prognosis of eating and swallowing function at discharge by using the results of the BSA on admission and evaluating the clinical course of eating and swallowing function at 4 weeks after admission.